Plasma cystine concentration and redox state in aging and physical exercise - Hildebrandt, Wulf; Kinscherf, Ralf; Hauer, K.; Holm, Eggert; Dröge, Wulf (Mechanisms of ageing and development, 2002)
Because redox-regulated signalling pathways are often modulated by the thiol/disulfide redox state (REDST), changes in plasma REDST may possibly account for pathological processes. We, therefore, investigated the mechanisms that account for changes in the plasma REDST as derived in first approximation from the cystine and acid soluble thiol (mainly cysteine) concentrations. Elderly subjects (studies A) and younger subjects after intensive physical exercise (IPE) (study B) i.e. subjects in conditions typically associated with decreased insulin responsiveness, showed, on the average, an increase in the plasma total free amino acid (TAA) concentration to approximately 3000 μM, including an increase in cystine but no increase in the thiol concentration if compared with controls. The REDST was decreased accordingly. A study on the postabsorptive amino acid exchange rates across the lower extremities (study C) indicated that a TAA level ⩾2800 μM supports a balanced net protein synthesis even under conditions of weak insulin stimulation, suggesting that high TAA levels may prevent the release of cysteine into the blood in the postabsorptive state. Collectively, these studies indicate that the age-related oxidative shift in plasma REDST may result from the decrease in amino acid clearance capacity and may be aggravated by excessive physical exercise.
Gesehen am 03.02.2021